數位課程圖像引導游標對學習注意力與學習成效影響之研究Effect of e-Learning Course Design with Guided Pointer on Students' Locus of Attention and Learning Achievement - 潘鈺筠Yu-Yun Pan; 林紀慧（通訊作者）Chi-Hui Lin (Higher Education Foundation, 2011)
本研究利用眼動儀觀察學習者於觀看數位課程圖像與閱讀過程中，眼睛觀看位置與眼球運動的情形。透過不同設計的數位課程介面，探討學習者於數位課程學習時的狀況與學習成效，輔以問卷評量與訪談。研究結果顯示：數位課程使用移動指示游標，對學習者的注意力分布具有顯著影響，並且會影響學習者觀看課程時的平均掃視幅度，對學習成效則不具影響。整體而言，學習者對數位課程畫面的滿意度除「訊息配置」之外，其他各項有指標組都高於無指標組。An eye tracker was used in this study to detect the effect of instruction design of e-Learning with or without using the guided pointer on learner's locus of attention and learning achievement. The results of the experiment found e-Learning instruction with guided pointer would significantly increase learner's locus of attention, but have no effect on learning achievement. However, the learning attitudes of the deceptive data revealed that learners in the indexing pointer group have higher scores than that of in the group without indexing pointer.